A Systematic Review on the Role of Advanced Glycation End-products (AGEs) in the Development of PCOS - Akhtar, Yasmin; Malik, Salma; Bhutta, Muna; Almanan, Sara Mohammed Atta; Solehria, Tahira Bashir; Malik, Muhammad Kashif (Journal of Liaquat University of Medical & Health Sciences, 2024)
This review was done to investigate the research done globally and in Pakistan about the role of AGEs in developing PCOS. Literature was searched at any time by using Google Scholar and PubMed. Keywords used were “PCOS”, “polycystic ovarian syndrome”, “Advanced glycation end-products”, “AGEs”, and “Pakistan”. Inclusion criteria were original research on humans, animals, or cell culture, showing the effect of AGEs on ovarian tissue. No research was found in Pakistan, emphasizing the point that Pakistan does not take the issue of AGEs seriously. All that was found was the relationship of AGEs with cardiovascular diseases or the prevalence of PCOS in Pakistani women. The original research done elsewhere globally was included in this review. Eighteen research studies have been conducted since 2000, including the relationship of AGEs with PCOS. Five studies found higher levels of AGEs in the blood and ovaries of patients with PCOS compared to controls. Three studies showed that dietary AGEs were directly associated with PCOS. Five animal (rats/mice) studies showed the effect of a diet high in AGEs on the ovaries of mice. Three cell line studies also showed a relationship between AGEs and ovarian tissues. Almost all human, animal, or cell-line studies showed the relationship of AGEs on the morphology or functioning of ovarian tissue. An easier way to prevent PCOS might be to control the AGE content in the diet.